Diabetogenic action of purified anterior pituitary hormones - Houssay, Bernardo A. (1949)
This communication deals with the diabetogenic action of three of the anterior pituitary hormones, namely growth hormone, adrenocorticotrophic hormone (ACTH) and prolactin. Previous work has indicated that purified growth hormone is diabetogenic (Marx et al., 1943; Houssay, 1945). The growth hormone, which had been prepared by Armour and Co. (lots #8KR32 and #3PKR3) exhibited a purity, as judged by the electrophoretic diagram, of approximately 84 per cent of a single component which had a mobility comparable to that of purified growth hormone. Assay of the material in a 60–70 gram hypophysectomized rat showed that a 50 gamma dose per day caused a body increment of 1.0 gram per day. The ACTH, which was also supplied by the Armour Laboratories (lot #45-A-4), had been prepared by a modification of the Sayers method. Biological assay on hypophysectomized rats, making use of the ascorbic acid depletion method of Sayers et al. (1948), showed a potency of 96 per cent.